EVALUASI KEBIJAKAN PENGGABUNGAN SEKOLAH DASAR NEGERI KOTA PEKALONGAN TAHUN 2013 - Jihan Amalia Syahidah; Priyatno Harsasto; Lusia Astrika (Journal of Politic and Government Studies, 2015)
Based on the data about Elementary School in Pekalongan City was discovered some problems up until now been homework for the Goverment of Pekalongan City especially the problems of infrastructure and facilities, teachers, and equitable access to quality education. Because of those problems, the Goverment of Pekalongan City in 2013 made policies that aim to create Elementary school that is effective and efficient based on the decision of Pekalongan Mayor number 421.2 / 151/2013 aboutpoliciesin combining elementary schools in Pekalongan city environment which is done in two ways: CombiningElementary school based on a pure region conducted in 40 schools that produced 16 State Elementary School and 16 principals and combining elementary school by one management conducted in 46 of state elementary schools and produced 23 principals and 46 elementary schools.The approach used in this research is descriptive qualitative with data collection methods such as observation , documentation and interview. The research subjects were Office of Education, Youth and Sports (Dinas Pendidikan Pemuda dan Olahraga)Pekalongan and all of the State Elementary School as the policies result combining a State Elementary School policies in Pekalongan with the unit of analysis of four elementary schools as a result of the combinationby pure region and four elementary schools based on the result of combining the management of four different sub-districts.The evaluation result of policies shows the difference between input that was given by a combination school based on management with combination school based on pure region. This difference makes a combination schoolby pure region is more effective and efficient, whereas the effectiveness combination school by management hasn’t yet been reached maximum. Moreover, this policy is not participatory but top down that means there’s no involvement of implementing policy in the policy formulation process.This research recommend that the need of the re-assesment about combination school based on management because this policy has not been proved able to answer the the problems of education in Pekalongan City, meanwhile for the policy about combination school based on pure region was already good enough in realizing an effective and efficient education in Pekalongan City.Key words : Effective and efficient, evaluation, Pekalongan City, Elementary school, Combining School